2000
DOI: 10.1074/jbc.275.20.14865
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Control of Multidrug Resistance by the Sit4 Protein Phosphatase in Kluyveromyces lactis

Abstract: The nuclear gene encoding the Sit4 protein phosphatase was identified in the budding yeast Kluyveromyces lactis. K. lactis cells carrying a disrupted sit4 allele are resistant to oligomycin, antimycin, ketoconazole, and econazole but hypersensitive to paromomycin, sorbic acid, and 4-nitroquinoline-N-oxide (4-NQO). Overexpression of SIT4 leads to an elevation in resistance to paromomycin and to lesser extent tolerance to sorbic acid, but it has no detectable effect on resistance to 4-NQO. These observations sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 83 publications
(85 reference statements)
1
10
3
Order By: Relevance
“…ABC transporter genes are regulated by protein phosphatase, which may activate expression of the transporter genes or may modulate the drug-pumping activity or substrate specificity of the transporters. It was demonstrated that increased expression of Sit4 protein phosphatase conferred PMM resistance in Kluyveromyces lactis, mediated by ABC transporters (25). Here we observed a marked increase in the expression of protein phosphatase 2A (a Sit4 protein phosphatase homologue in Leishmania) in paromomycin-resistant L. donovani, compared with its sensitive counterpart.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…ABC transporter genes are regulated by protein phosphatase, which may activate expression of the transporter genes or may modulate the drug-pumping activity or substrate specificity of the transporters. It was demonstrated that increased expression of Sit4 protein phosphatase conferred PMM resistance in Kluyveromyces lactis, mediated by ABC transporters (25). Here we observed a marked increase in the expression of protein phosphatase 2A (a Sit4 protein phosphatase homologue in Leishmania) in paromomycin-resistant L. donovani, compared with its sensitive counterpart.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, protein phosphatase 2A, which has a probable role in activating the expression of these transporters (25), was found to be highly upregulated (4.47 Ϯ 0.71-fold) in PMM-R parasites (Fig. 3).…”
Section: Resultsmentioning
confidence: 97%
“…In previous work it was indicated that the Sit4 protein phosphatase of K. lactis plays a critical role in controlling drug transport (9). This finding makes K. lactis an attractive model system for investigating the novel regulatory mechanism of MDR for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…SIT4 has been found to have a broad role in regulating MDR (9). It negatively regulates the resistance of cells to oligomycin, antimycin, ketoconazole, and econazole and positively modulates tolerance to paromomycin, sorbic acid, and 4-nitroquinoline-N-oxide.…”
mentioning
confidence: 99%
“…Such a pathway could involve another transporter in yeast, which probably has a weaker affinity to transport arsenite. This is a likely possibility as many transporters have a broad range of substrate specificity, for example, Yor1 (Chen et al 2000).…”
Section: Figmentioning
confidence: 99%